Planktonic Foraminifera Biostratigraphy of the Pliocene Kintom and Bongka Formation, Central Sulawesi, Indonesia - Novian, Moch. Indra; Barianto, Didit Hadi; Husein, Salahuddin; Surjono, Sugeng Sapto (Universitas Gadjah Mada, 2024)
The Pliocene sediments exposed in the eastern arm of southern Sulawesi consist of Kintom and Bongka Formations, thought to be the result of collisions in the Middle Miocene. The research area is located along the Matindok – OndoOndolu road, Banggai Regency, Central Sulawesi Province. The aims of the research is to determine the rock units that developed in the Kintom – Bongka Formation and determine the chronological time frame based on planktonic foraminifera biostratigraphy. This research used stratigraphic measurement on a scale of 1:100 and Plio-Pleistocene planktonic foraminifera biostratigraphy. A lithological column along 315 meters divided into three rock units. The marl unit and calcareous sandstone unit show characteristics similar to flysch deposits from the collision and are part of the Kintom Formation. Intergrade conglomerate gravelly sandstone deposited unconformably on top of the previous unit is part of the Bongka Formation. This last unit shows characteristics similar to molasse deposits. In total of 46 rock samples were analyzed for foraminifera biostratigraphy. Seven foraminifera biozones showing the age of rock deposition from the Early Pliocene to the Late Pleistocene.The order of the foraminifera biozone is Globorotalia tumida Brady LOZ (PL1a; 5.59 - 4.45 Ma), Globoturborotalita nepenthes Todd CRZ (PL1b; 4.45 - 4.39 Ma), Globotalia acostaensis Blow PRZ (PL2a; 4.39 – 4.31 Ma), Globotalia margaritae Bolli HOZ (PL2b; 4.31 - 3.85 Ma), Sphaeroidinellopsis seminulina Schwager HOZ (PL 3-4; 3.85 – 3.20 Ma), Globorotalia (M) miocenica Palmer/Globorotalia miocenica Palmer HOZ (PL5–6; 3.20 – 2.30 Ma), and Pulleniatina praecursor Banner & Blow HOZ (PL6–PT1a; 2.30 – 2.26 Ma).